Two for one: Diffusion models and force fields for coarse-grained molecular dynamics - Arts, Marloes; García Satorras, Victor; Huang, Chin-Wei; Zügner, Daniel; Marco Federici; Clementi, Cecilia; Noé, Frank; van den Berg, Rianne; Pinsler, Robert (Journal of Chemical Theory and Computation, 2023)
Coarse-grained (CG) molecular dynamics enables the study of biological processes at temporal and spatial scales that would be intractable at an atomistic resolution. However, accurately learning a CG force field remains a challenge. In this work, we leverage connections between score-based generative models, force fields and molecular dynamics to learn a CG force field without requiring any force inputs during training. Specifically, we train a diffusion generative model on protein structures from molecular dynamics simulations, and we show that its score function approximates a force field that can directly be used to simulate CG molecular dynamics. While having a vastly simplified training setup compared to previous work, we demonstrate that our approach leads to improved performance across several small- to medium-sized protein simulations, reproducing the CG equilibrium distribution, and preserving dynamics of all-atom simulations such as protein folding events.